2021
DOI: 10.5713/ajas.19.0932
|View full text |Cite
|
Sign up to set email alerts
|

Complete mitochondrial genome sequence of Tosa-Jidori sheds light on the origin and evolution of Japanese native chickens

Abstract: 14 15 ORCID 16 Sayed A.-M. Osman: https://orcid.org/0000-0001-6925-9414 ABSTRACT 27 Objective: In Japan, approximately 50 breeds of indigenous domestic chicken, called Japanese native 28 chickens (JNCs), have been developed. JNCs gradually became established based on three major 29 original groups, "Jidori", "Shoukoku" and "Shamo". Tosa-Jidori is a breed of Jidori, and archival 30 records as well as its morphologically primitive characters suggest an ancient origin. Although Jidori 31 is thought to have been i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…SNPs have been used for genomewide analysis to assess the conservation status and the genomic variability of Italian chicken breeds [22] as well as to understand genetic structures of these (indigenous, commercial, gamecock, and wild ancestral chicken) breeds under different selection pressure [23]. Furthermore, mitogenome sequences have been utilized to assess hereditary divergence between 22 Asian native breeds and seven native Indian chicken breeds [24], to investigate phylogenetic evolution and genetic diversity of Tibetan chicken [25], Tosa-Jidori of Japan [26], Huainan Partridge [27], and Huangshan Black [28] chickens of China. However, microsatellites and DNA barcodes still accepted as markers of choice because they are technically less demanding and cost-effective in evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…SNPs have been used for genomewide analysis to assess the conservation status and the genomic variability of Italian chicken breeds [22] as well as to understand genetic structures of these (indigenous, commercial, gamecock, and wild ancestral chicken) breeds under different selection pressure [23]. Furthermore, mitogenome sequences have been utilized to assess hereditary divergence between 22 Asian native breeds and seven native Indian chicken breeds [24], to investigate phylogenetic evolution and genetic diversity of Tibetan chicken [25], Tosa-Jidori of Japan [26], Huainan Partridge [27], and Huangshan Black [28] chickens of China. However, microsatellites and DNA barcodes still accepted as markers of choice because they are technically less demanding and cost-effective in evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…These results were consistent with the findings of previous studies (Colli et al, 2015;Mustafa et al, 2022) when they found similar maternal lineages in goats using the complete mitogenome. Using nucleotide polymorphisms found in mtDNA sequences, phylogenetic relationships based on the diversity of maternal lineages can be utilized to retrace the origins and genealogy of various domestic animals (Naderi et al, 2007;Lippold et al, 2011;Mustafa et al, 2018;Osman et al, 2021). MtDNA is widely employed to generate phylogenetic trees at various taxonomic levels, from within species to among mammalian orders (Bruford et al, 2003).…”
Section: Phylogenetic Relationships Based On the Assessment Of Comple...mentioning
confidence: 99%
“…Serving as an independent repository of genetic information, mitochondrial genomes are inherited maternally, evolve rapidly, and lack recombination. Consequently, they are frequently employed as genetic markers with significant applicability in studies related to population genetics, ecological genetics, phylogeny, and evolutionary analysis [ 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%